Physiological changes and sleep responses during and following a world record continuous walking record. Issue 3 (September 1984) - Davies, B.; Shapiro, C. M.; Daggett, A.; Gatt, J. A.; Jakeman, P.
Abstract : Physiological changes, and subsequent sleep responses, were recorded in a male subject during and following 338 miles of continuous walking and consequent sleep deprivation. One hundred and thirty hours of walking and a seventy-two hours post-walk recovery period were monitored. The subject walked at approximately 55% of maximum oxygen uptake (VO2 max), heart rate ranged between 102-106 b/min, and blood lactate (LA) remained below the 2 mmol/l level. No electrocardiograph abnormalities were observed either during the walk or pre- and post-functional diagnostic graded exercise test (FDGXT). Creatine kinase (CK) and creatine kinase isoenzyme (CK-MB) levels rose throughout the walk but exhibited differing depletion patterns. The ratio of CK-MB to CK (MB/CK%) did not exceed levels which are suggestive of myocardial ischaemia. Haematological variables demonstrated signs of anaemia towards the end of the walk. Catecholamine levels rose throughout the walk, with greater rises being observed in nor-adrenaline and dopamine. During the post-walk recovery phase, adrenaline concentration remained elevated. Following this extreme period of exertion, the subject demonstrated very short sleep latency and rapid entry into slow wave sleep (SWS). These sleep patterns were compared to sleep recordings made over a similar period (72 h) six months post-walk, when the subject was not exercising. Nocturnal growth hormone (GH) levels were significantly raised on the post-walk nights.